The effect of NFA buffer stock actions on the prices of rice in the Philippines - Andrada, Garizaldy A.
The study was conducted to examine the effect of NFA buffer stock actions on palay procurement and rice distribution on the prices of rice at the farmgate and retail levels in the Philippines. The study used annual and monthly prices of rice, annual NFA palay procurement and rice distribution, and NFA monthly stock inventory to empirically measure the influence of government buffer stock programs on annual and monthly variability of farmgate and retail rice prices. Annual NFA palay procurement and rice distribution showed no significant stabilizing influence on the price changes of rice at the farmgate and retail levels. Meanwhile, NFA monthly stock inventory showed only significant stabilizing effect on the monthly retail prices of rice.